Deportation Decisions: Judicial Decision-Making in an American Immigration Court. (August 2019) - Asad, Asad L.
Drawing on ethnographic observations and informal conversations with judges in Dallas Immigration Court, as well as archival documents, this article describes two approaches through which judges in this setting justify their decisions during removal proceedings. The "scripted approach, " used to effect the routine removal of noncitizens in most of the completed cases observed, entails judges' recitation of well-rehearsed narratives regarding the limited legal rights and remedies available to noncitizens. The "extemporaneous approach" involves judges moving beyond their scripts and deliberating in greater depth about noncitizens' cases. In doing so, judges' personal attitudes, biases, and motivations are often revealed as they articulate their desire to circumvent the removal process for noncitizens they view as "deserving" of relief—but for whom only temporary relief from removal is often available given judges' interpretations of immigration law. Although judges recognize that this temporary relief may allow some noncitizens to remain in the United States indefinitely, incomplete protection from removal can leave noncitizens in a precarious legal status and jeopardize these individuals' future opportunities for legalization. These findings support a conceptualization of immigration judges as street-level bureaucrats, or frontline workers who interpret the law—sometimes unevenly—to enforce government policy while interfacing with the individuals subject to said policy. The study thus amplifies the social control capacity of the federal immigration regime.